Effect of hard metal dust on ventilatory function. Issue 7 (July 1986) - Kusaka, Y; Ichikawa, Y; Shirakawa, T; Goto, S
Abstract : The effect of hard metal dust generated in shaping on ventilatory function has been studied, in particular, the relation between levels of exposure to cobalt and changes in ventilatory function. In 15 healthy young men a significant decrease in FVC occurred after a six hour exposure to hard metal dust containing cobalt at a mean concentration of 38 micrograms/m3 (range 14-76 micrograms/m3). No dose-effect relation could be discerned between the decrease in FVC and the hard metal concentration or the cobalt concentration. All the subjects complained of irritation of the airways. On the other hand, in 42 shaping workers exposed to cobalt at an average concentration of 85 micrograms/m3 no significant decreases in ventilatory function were detected after seven hour exposures to hard metal, although in 42 shapers, who had been exposed to cobalt at a mean concentration of 126 micrograms/m3, the FEV1% was significantly decreased compared with matched controls. This finding suggests that hard metal dust containing cobalt at a mean concentration of 126 micrograms/m3 causes chronic bronchial obstruction.